Den Stier das Tanzen lehren? Europa vor neuen Herausforderungen - Fisahn, Andreas (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2012)
The crisis of the European Union cannot be solved by austerity programs. Therefore a closer look at the reasons of the crisis seems to be reasonable, which includes a description of the development of the EU from 1951 to present times. The Union started as a tariff union and evolved through different steps to an order of competitive states. The main fields of competition between the states are taxes and social costs, which leads to tax dumping and a race to the bottom in social benefits. Starting in 1990 the EU achieved the status of an open financial market, with the duty of deregulation of capital movements being stipulated in Treaties. In the end the problem is not a debt crisis but a crisis of the structure of the European Union. The solution – which especially the German government prefers – may be the first step on the way to an authoritarian state.